The detection of porosity on designed references samples with various porosity levels produced by 3D printing to investigate the accuracy of computed tomography (CT) scans (XTH225ST) - Muhammad Faris Asnin (2018)
Non-destructive testing (NDT) is a technique used to analyse the internal and external features of a part without causing any damage to it. There are wide varieties of NDT methods being practiced in the different engineering fields and for this project, we will be investigating mainly on Computed Tomography (CT) scanning and the experiment of Archimedes’ Principle. In contrast to other NDT scanning methods, CT scan is capable of scanning and reconstructing the scanned image into a full 3D image with all the internal and external features of the part. Hence, it helps to reveal any defects or porosities that maybe present in it. For this project, the author will be investigating on the accuracy of a CT scan machine; Nikon XTH225ST. A comparison will be made based on the results obtained between Archimedes’ Principle and CT scan and the author is interested to find out what is the deviation of the CT Scanning machine capabilities as compared to the theoretical results. Therefore, for this project, 3D printed specimens with different percentages and sizes of designed porosities will be used for analysis. Each specimen with different porosities will be analysed and a comparison between theoretical data from the CAD model and the results obtained through CT scanning will be made.